Analisis Sistem Penunjang Keputusan Penerimaan Beasiswa Kartu Indonesia Pintar Kuliah di Universitas Graha Nusantara Menggunakan Metode Copras - alwendi; Lela Budiarti; Andi Saputra Mandopa (Politeknik Negeri Media Kreatif, 2025)
This study aims to build a decision support system in KIP scholarship acceptance at Graha Nusantara University Using the Copras Method. Acceptance of the Smart Indonesia Card (KIP) scholarship at universities often faces challenges in determining prospective recipients who best meet the criteria objectively and transparently. To overcome this problem, in order to facilitate work and avoid data calculation errors with the old system, a decision support system was built that can help make decisions about KIP recipients quickly and more accurately using the Complex Proportional Assessment (COPRAS) method. The COPRAS method was chosen because it is able to handle the multi-criteria decision-making process by considering the weight of interest of each alternative assessed. This system is designed to process various scholarship selection parameters, such as economic conditions, academic achievement, and other additional criteria, in order to produce a more accurate and fair ranking of prospective scholarship recipients. The results of the study show that the application of the COPRAS method in the SPK can increase efficiency and objectivity in the KIP scholarship selection process, which are the variables or criteria for this study, there are 5 criteria, namely, Academic achievement, Parental dependencies, Student ability, Parental income, Distance of residence. From the results of the research conducted, it can be concluded that this method is able to provide good results and is close to the results of the assessment used by the Campus. This research can provide effective KIP Scholarship Acceptance results according to the Copras model test with a value of 99.972. This decision support system is expected to help make it easier to select students who are eligible for KIP